2000
DOI: 10.1111/j.1471-0528.2000.tb13307.x
|View full text |Cite
|
Sign up to set email alerts
|

Car seatbelts in pregnancy: the practice and knowledge of pregnant women remain causes for concern

Abstract: ObjectiveDesign A structured questionnaire. Setting District hospital antenatal clinic.Participants Two hundred pregnant women attending for their routine mid-pregnancy anomaly scan. Main outcome measuresTo evaluate current knowledge and practice among pregnant women about the use of car restraint systems during pregnancy.The women were asked about seatbelt and airbag usage, source of information about restraint systems and the legal requirements and recommendations regarding car safety systems.One hundred fif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 29 publications
2
22
0
1
Order By: Relevance
“…in 40% to 50% of pregnant women. 5,6 Various other studies have shown reduced seatbelt compliance during pregnancy. 7 The proportion of seatbelt use has been reported to be around 70% to 80% before pregnancy, but reduced by half at 20 weeks or more of gestation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…in 40% to 50% of pregnant women. 5,6 Various other studies have shown reduced seatbelt compliance during pregnancy. 7 The proportion of seatbelt use has been reported to be around 70% to 80% before pregnancy, but reduced by half at 20 weeks or more of gestation.…”
Section: Introductionmentioning
confidence: 99%
“…5,7 There is also evidence that pregnant women lack information about the proper use of a seatbelt and its role in preventing injury: only 14% to 37% of pregnant women received advice from health care professionals. [5][6][7][8] The common reasons for not using a seatbelt have been reported to include discomfort, inconvenience, forgetfulness, and fear of harming the fetus. 9 In this study, the current practice and knowledge of Hong Kong pregnant women about seatbelt use was surveyed, and any determining factors were identified.…”
Section: Introductionmentioning
confidence: 99%
“…However, this did not clearly distinguish between the (incorrect) position 'lap belt across the upper thighs' and the correct position according to guidelines 'across the hips'. Therefore, it is not surprising that Arneson et al [14], Hammond et al [15], Johnson and Pring [11], and McGwin et al [18] reported a high incidence of correct lap belt positioning such as approximately 40-79%. In this study, the incorrect 'flat across the upper thighs' and correct 'across hips and under abdomen' data are classified into two separate groups in order to investigate the real correct use rate of the lap section.…”
Section: Comparison With Previously Published Studiesmentioning
confidence: 99%
“…Motor vehicle accidents account for 60% of blunt traumas [1]. Pregnant women are less likely than other motorist to wear seatbelts because of concerns of fetal injury [35,36]. If they wear seatbelts they are often applied over the wrong site, potentially leading to increased fetal mortality [36].…”
Section: Blunt Abdominal Traumamentioning
confidence: 99%
“…Pregnant women are less likely than other motorist to wear seatbelts because of concerns of fetal injury [35,36]. If they wear seatbelts they are often applied over the wrong site, potentially leading to increased fetal mortality [36]. The ACOG and the RCOG have now produced speciWc guidelines reassuring pregnant women about the use of seatbelts reviewing the safety and beneWt of correctly applied three-point safety restraints [37,38].…”
Section: Blunt Abdominal Traumamentioning
confidence: 99%